Utilization of computer technology in learning transformation - Abu Bakar, Kamariah; Mohd Ayub, Ahmad Fauzi; Ahmad Tarmizi, Rohani (2010)
The integration of technological tools especially computer software may contribute to creating powerful learning environments in numerous ways especially in the teaching and learning of mathematics. Utilization of computer technology to enhance students understanding of mathematics has been widely practised. Various types of dynamic mathematical software such as Geometer’s Sketchpad, Autograph and the Graphing Calculator have been utilized for the learning of mathematics in Malaysian secondary schools. However, the use of an open source software in teaching and learning mathematics is still new in Malaysia. This paper compare the effectiveness of an open source software, GeoGebra and two coursewares (e-transformation and Vtransformation) developed by the researchers for learning transformation. A total of 101 secondary school students participated in the study. They were randomly assigned into three separate groups. Each group underwent instruction utilizing one of the three coursewares. Findings showed that significant differences existed between the pre and post test of the performance scores of each group that used GeoGebra, e-transformation and Vtransformation. However, there was no significant difference in the post test performance scores of the three groups. Further analysis also showed that there was no significant difference in the post test scores of each of the three topics included in the software. These findings had shown that computer technology was effective in teaching mathematics at Malaysian secondary school level. However, the findings did not indicate which software was more suitable to be used in the teaching and learning transformation.